Analysis of Lymphocyte Immunological Reactivity in Patients with Pleural Effusions of Different Aetiology - Goseva, Zlatica; Jovkovska Kaeva, Biserka; Gjorcev, Angelko; Jovanovska Janeva, Elena; Arsovski, Zoran; Sava Pejkovska; Tatabitovska, Aleksandra (ID Design 2012/Scientific Foundation SPIROSKI, 2016)
BACKGROUND: The proportion of T and B lymphocytes in pleural fluids and blood may point to the presence of local immunological phenomena in pleural disorders.AIM: Aim of study was to evaluate the lymphocyte phenotype and the ratio between helper (CD4+) and cytotoxic/suppressor (CD8+) lymphocytes in malignant and non-malignant effusions.MATERIAL AND METHODS: We studied 48 patients with pleural effusions. First group had 18 patients with tuberculosis pleural effusions; second group had 20 patients with malignant pleural fluids, third group had 10 patients with transudates and 30 healthy controls. We investigated the distribution of T and B lymphocytes, T cells with helper/inducer CD4 or suppresser/cytotoxic CD8 phenotypes and the CD16 subset.RESULTS: Results showed decreases levels ofCD3, CD4, and CD16 T cells in blood of patients versus healthy controls. There were increases in the percentage of the CD3 and CD4 T cells in the pleural fluid compared with values in the blood with statistical significance in tuberculous pleurisy. The values of CD8 were similar in the pleural fluid and in blood. Levels of CD16 were non-significantly higher in pleural fluid in all groups.CONCLUSION: This study confirms the hypothesis that pleural cavity is compartment with immunological reactivity and results could be used in differential diagnosis together with other examinations.IntroductionLymphocytes are the primary effectors of cellular and humoral immunocompetence in humans. Lymphocytic pleural effusions are characterized by divergent cellular responses depending on the etiology of disease[1]. The accumulation of fluid in the pleural space indicates the presence of systemic or local disease. Pleural exudates involve the migration of immune cells to the pleural cavity[2]. Lymphocytes dominance occurs in the most chronic pleural effusions[3, 4]. The proportion of T and B lymphocytes in pleural fluids relative to that in peripheral blood may point to the presence of local immunological phenomena in various pulmonary and pleural disorders. Tuberculosis and malignant disease are among most frequent causes of pleural effusions. In both causes, the pleural fluid is generally lymphocytic, with predominance of T lymphocytes, particularly CD4+ positive T cells[2, 5, 6]. Malignant effusions are a relatively easily accessible source of tumor-associated T cells andthis represent a suitable model for the study of interactions between tumor cells and the host immune system[7]. Considering the compartmentalization of the pleural space, the association between the local and systemic cellular responses should be analyzed.
Keywords: pleural effusions; lymphocyte; CD markers; malignant pleural fluid; tuberculous pleural effusions